Unable to Find a Research Title? - Bhandari, Bal Mukunda (Journal of NELTA Surkhet, 2015)
Most of the Master’s students who opt for thesis writing could not find an appropriate title for them, and they ask their supervisors, professors and seniors for a title. Similarly those who are aspiring for a Ph.D. cannot start the work because they are unable to find a suitable title for them. When I ask my colleagues and students to go for Ph.D., to carry out classroom research and other small scale research, to write research article, they say that they have no idea on what to write, and they ask me to provide them with a topic for the research. This article, based on my experience of supervising and evaluating theses, is an attempt to help Master’s and Ph.D. students in general and M.Ed. English students in particular, find a suitable title for their research. It discusses some sources, from which thesis titles come, viz. problem, curiosity, disagreement, courses of study, and previous works in the related field. Journal of NELTA Surkhet Vol.4 2014: 13-17